Dietary Chicory Inulin-Rich Meal Exerts Greater Healing Effects than Fructooligosaccharide Preparation in Rats with Trinitrobenzenesulfonic Acid-Induced Necrotic Colitis - Bartosz Fotschki; Adam Jurgoński; Joanna Fotschki; Michał Majewski; Katarzyna Ognik; Jerzy Juśkiewicz (Polish Journal of Food and Nutrition Sciences)
The aim of the study was to compare the effects of chicory root inulin-rich meal (containing polyphenolic fraction as well) and pure fructooligosaccharides (FOS) on necrotic colitis induced with trinitrobenzenesulfonic acid (TNBS) in Wistar rats. Both chicory preparations significantly reduced the pH of colonic digesta and favourably lowered the caecal activity of bacterial β-glucuronidase as well as the caecal concentration of putrefactive short-chain fatty acids in comparison to the control TNBS rats. Both chicory preparations enhanced the production of total short-chain fatty acid (SCFA pool) and concentration of anti-inflammatory propionic acid in the caecal digesta. Nevertheless, only dietary chicory meal favourably increased the total SCFA concentration and thus decreased the pH of caecal digesta. Increased caecal SCFA production may explain observed greater reduction in mucosal necrosis and increase in glandular mucosal regeneration in rats fed a diet with chicory root meal. Both chicory preparations beneficially regulated physiological parameters in the lower part of the rat intestinal tract after TNBS-induced colitis, however the dietary treatment with chicory meal showed stronger reduction of mucosal disturbances caused by colitis. Those beneficial effects might be related to higher polymerization of inulin vs. FOS and presence of biologically active compounds in the meal, i.e., phenolic compounds, which have strong impact on intestinal microbial activity and thus indirectly alleviated mucosal disturbances caused by colitis.